The effects of slope gradient and soil depth on soil physicochemical properties in the Achew small-scale irrigation area, Southwest Ethiopia - Wasihun Mengiste; Dereje Tsegaye; Samuel Dagalo; Teshome Yitbareke (PLoS ONE, 2025)
For sustainable land management, clear information about landscapes and soil depth is crucial. The purpose of this study was to investigate how slope variation and soil depth affect selected physicochemical properties of soil in the Achewa irrigated area of the Itang Special District in the Gambella region southwest of part of Ethiopia. Soil samples were collected from three topography positions (lower, middle, and upper slope locations) and on both soil samplings (0–20 cm and 20–40 cm). A total of 18 composite soil samples were collected from three slope gradients and two soil depths with three replications by auger for soil physical and chemical properties. Correspondingly, 18 undisturbed samples were taken for soil BD and TP determination by the core sampling method. Standard laboratory methods were used to analyze the collected soil samples. The data were analyzed using the General Linear Model (GLM) procedure in SAS version 9.4. The result showed that slope gradients, soil depths, and slope gradients interacting with soil depths had very highly, highly and significant effects on selected soil parameters, exchangeable bases, and extractable micronutrients. The highest percentage of sand fraction (32.00%) and BD (1.37) were recorded on the upper slope gradients. Beside the highest percentage of clay content (58.17%), TP (51.32%), pH (7.28), OM (3.52%), TN (0.21%), AV.P (26 ppm), exchangeable Ca (8.55 mg/l), Na (0.69 mg/l), K (0.43 mg/l), CEC (28.96 cmol (+) kg ⁻ ¹), PBS (56.44%), extractable Fe (15.78 mg kg ⁻ ¹), Mn (11.08 mg kg ⁻ ¹), and Cu (2.82 mg kg-1) were observed on the lower slope gradient, while, except for the sand fraction, BD, and extractable Zn, which are lowest on the lower slope gradients, all the above-listed parameters were lowest on the upper slope gradient. In terms of soil depth, the sand fraction, TP, Av. P, TN, CEC, OM, extractable micronutrients like Fe, Mn, Cu, and Zn decreased with increasing soil depth, while the clay content, BD, pH, and exchangeable bases like Ca, Mg, Na, and K were increased with increasing soil depth. Regarding interaction effects, the highest TP, pH, OM, TN, AV.P, CEC, and extractable Mn, were observed on the lower slope gradient of surface (0–20 cm) soil depth. Generally, slope gradient and soil depth, and to some extent the interaction effect of slope gradient with soil depth, cause variations in physicochemical properties of the soil, exchangeable bases, and extractable micronutrients of the study area.